Diversity and environmental distribution of Asgard archaea in shallow saline sediments - Hager, Karin; Luo, Zhen-Hao; Montserrat-Diez, Marina; Ponce-Toledo, Rafael I.; Baur, Pamela; Dahlke, Sven; Andrei, Adrian-Stefan; Bulzu, Paul-Adrian; Ghai, Rohit; Urich, Tim; Glatzel, Stephan; Schleper, Christa; et al. (Frontiers in Microbiology, 2025)
In recent years, our understanding of archaeal diversity has greatly expanded, especially with the discovery of new groups like the Asgard archaea. These archaea show diverse phylogenetic and genomic traits, enabling them to thrive in various environments. Due to their close relationship to eukaryotes, a large number of metagenomic studies have been performed on Asgard archaea. Research on the fine scale distribution, diversity and quantification in saline aquatic sediments where they mostly occur, has, however, remained scarce. In this study, we investigated depths of shallow saline sediment cores from three distinct European environments: the Baltic Sea near Hiddensee, the coastal Lake Techirghiol in Romania, and an estuarine canal in Piran, Slovenia. Based on 16S rDNA amplicon sequencing, we observe variation in the relative abundance and occurrence of at least seven different Asgard groups that are distinct between the three environments and in their depth distribution. Lokiarchaeia and Thorarchaeia emerge as dominant Asgard groups across all sites, reaching maximal relative abundances of 2.28 and 2.68% of the total microbial communities respectively, with a maximal abundance of all Asgard reaching approx. 5.21% in Hiddensee. Quantitative PCR assays provide insights into the absolute abundance of Lokiarchaeia, supporting distinct patterns of distribution across depths in different sediments. Co-occurrence network analysis indicates distinct potential microbial partners across different Asgard groups. Overall, our study shows that Asgard archaea are found as a stable component in shallow sediment layers and have considerably diversified on macro- and microscales.